Exploring consumers attitude towards web advertising and its influence on web ad usage in Malaysia - Norzalita Abd Aziz,; Ahmad Azmi M. Ariffin, (Penerbit Universiti Kebangsaan Malaysia, 2010)
The digital age has already made significant changes to each of the elements of the promotion mix. Companies increasingly see the Internet as an important medium through which advertising messages can be directed towards consumers. In the 21st century, consumers have more control over advertising exposure with web advertising because they can select how much commercial content they wish to view. However, very little is known of consumer beliefs about Web advertising, attitudes toward Web advertising or Web advertising associated with consumer behaviour in Malaysia. By adopting and applying Korgaonkar, Silverbatt and O’Leary’s measurements, this paper explores Web users’ beliefs, attitudes and use of Web advertising. The descriptive statistics, cross tabulation, factor analysis results as well as regression analysis and its implications on the findings are discussed